Examining How Students With Diverse Abilities Use Diagrams to Solve Mathematics Word Problems. (August 2013) - van Garderen, Delinda; Scheuermann, Amy; Jackson, Christa
This study examined students' understanding of diagrams and their use of diagrams as tools to solve mathematical word problems. Students with learning disabilities (LD), typically achieving students, and gifted students in Grades 4 through 7 ( N = 95) participated. Students were presented with novel mathematical word problem-solving tasks and interviewed for their understanding of diagrams for solving problems. Scoring rubrics were designed to assess for levels of problem-solving performance, evidence of diagram use, type of diagram generated, how the diagram was used to solve problems, their definition of a diagram, and their reason for why a diagram can be used to solve problems. Results indicated that students with LD typically generated diagrams of a poorer nature and used them in a less strategic manner than their peers. Concerns regarding the impact of content knowledge on the quality of diagram generation as well as implications regarding instruction to use diagrams to understand and solve problems are discussed.